The rancher's redemption - Pearce, Kate, 1963- (Pearce, Kate, 1963- Millers of Morgantown., 2019)
Widowed for ten years, now running the family ranch, Adam Miller is no longer the fun-loving guy who married his high school sweetheart the moment they graduated. His bitterness in the aftermath of her death even alienated his closest link to her<U+2014>Lizzie Taylor, her best friend. But when Adam comes across Lizzie in a dire situation, he<U+2019>s compelled to help<U+2014>and finds himself with an unusual opportunity to make amends . . . A struggling single mom, Lizzie<U+2019>s extremely wealthy ex ran out on her when she got pregnant. But now he and his family have decided to fight for custody of her young son. When Adam shocks her by offering to pose as her partner, awkward as it may feel, it<U+2019>s Lizzie<U+2019>s best chance to hold onto her child. And as they strive to present a united front, their old friendship rekindles, sparking an unexpected attraction<U+2014>along with past hurts and secrets. Soon they realize they<U+2019>ll have to find a way to forgive if they want to move forward<U+2014>especially with each other . . .